2016
DOI: 10.1016/j.bbagrm.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

p53 represses the transcription of snRNA genes by preventing the formation of little elongation complex

Abstract: The regulation of transcription by RNA polymerase II (Pol II) is important for a variety of cellular functions. ELL/EAF-containing little elongation complex (LEC) was found to be required for transcription of Pol II-dependent small nuclear RNA (snRNA) genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Alternatively, the LEC may be involved in transcription of other classes of genes, for which ZC3H8 may play a more central role. Recently, p53 was demonstrated to disrupt the formation of the LEC by interaction with the ELL subunit, displacing it from interaction with ICE1 and leading to inhibition of expression of some snRNAs [ 47 ]. This interaction was also predicted to displace ZC3H8.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the LEC may be involved in transcription of other classes of genes, for which ZC3H8 may play a more central role. Recently, p53 was demonstrated to disrupt the formation of the LEC by interaction with the ELL subunit, displacing it from interaction with ICE1 and leading to inhibition of expression of some snRNAs [ 47 ]. This interaction was also predicted to displace ZC3H8.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that p53 represses the transcription of snRNA genes (67) and does so by preventing the little elongation complex from forming (68). It has been suggested that p53 dissociates ELL1 from the little elongation complex.…”
Section: Other Changes Associated With Stress That Could Change Snrnamentioning
confidence: 96%
“…It has also been reported that p53 represses the transcription of snRNA genes [77] and does so by preventing the little elongation complex from forming [78]. It has been suggested that p53 dissociates ELL1 from the little elongation complex.…”
Section: Other Changes Associated With Stress That Could Change Snmentioning
confidence: 99%